PERAN MAQASID SYARIAH DALAM MEWUJUDKAN KEUANGAN INKLUSIF: STUDI PEMBIAYAAN MIKRO PADA BANK MEKAR SYARIAH DI BURNEH, BANGKALAN - Esa Nurlaili; Rudi Hermawan; Ahmad Musadad; Agustina Kumala Dewi Sholihah (FASTABIQ: JURNAL STUDI ISLAM, 2026)
Inclusive finance is a national and global strategic agenda to increase access to financial services for the community that has not been served, especially micro business actors. In the context of sharia business law, maqashid sharia becomes a normative framework that can direct financial practices to not only be profit-oriented, but also ensure justice, blessings, and sustainability. This article aims to analyze the role of sharia maqashid in realizing inclusive finance through a case study of microfinance at Bank Mekar Syariah Burneh. The research uses a qualitative approach with case study methods through in-depth interviews, observations, and document analysis, which is then processed with Miles & Huberman data analysis techniques and source triangulation. The results of the study show that the implementation of maqashid sharia is reflected in the financing orientation that emphasizes the principles of justice, property protection (hifdz al-mal), improving the quality of life, and the sustainability of customer businesses. The sharia microfinance strategy has been proven to be able to expand access to finance, increase literacy, and strengthen the economic empowerment of small communities. This study confirms that the integration of sharia maqashid with inclusive financial indicators not only strengthens the sharia business legal literature, but also offers a microfinance model that can be replicated by other sharia financial institutions in Indonesia.